2013
DOI: 10.1111/cpr.12074
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis and G2/M cell cycle arrest by Scrophularia striata in a human leukaemia cell line

Abstract: Results of the study indicated that S. striata extract could inhibit leukaemia cell proliferation by inducing G2 /M phase arrest and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Moreover, some studies showed that other genus of scrophularia such as S. floribunda and S. striata extract induced apoptosis in tumor cells through induction of cell cycle arrest. 3,13 Our findings demonstrated that S. variagata extract can induce a G2/M phase cell cycle arrest in MCF-7 cells in a dose-dependent manner.…”
Section: Effect Of S Variagata Extract In Mcf-7 Apoptosis and Cell Cmentioning
confidence: 58%
See 2 more Smart Citations
“…Moreover, some studies showed that other genus of scrophularia such as S. floribunda and S. striata extract induced apoptosis in tumor cells through induction of cell cycle arrest. 3,13 Our findings demonstrated that S. variagata extract can induce a G2/M phase cell cycle arrest in MCF-7 cells in a dose-dependent manner.…”
Section: Effect Of S Variagata Extract In Mcf-7 Apoptosis and Cell Cmentioning
confidence: 58%
“…To confirm breast cancer apoptosis, we evaluated the fragmented DNA from MCF-7 cells by gel electrophoresis as previously described. 3 In addition, caspase-3 and caspase-9 activity were assessed according to the manufacturer's instruction of the caspase colorimetric assay kit (R&D systems).…”
Section: Dna Fragmentation Analysis and Measurement Of Caspase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that S. striata extract could inhibit leukaemia cell proliferation by inducing apoptosis [15] . However, in contrast to this finding there are studies showing that Scrophularia striata extract had no effect on cell viability [17].…”
Section: Discussionmentioning
confidence: 99%
“…Also the studies indicated that S. striata extract could inhibit leukaemia cell proliferation by inducing G2 /M phase arrest and apoptosis . [15] Other findings indicated that both leaves and seeds of S.Striata contain both anti cancer and cell growth enhancing agents [16]. But in other studies showed that s.striata in spite of using in trating inflammatory diseases but Scrophularia striata extract had no effect on cell viability [17].…”
Section: Introductionmentioning
confidence: 99%